Penerapan Metode Food Plating Untuk Meningkatkan Motivasi Siswa Dalam Menyajikan Masakan Indonesia - M. Hafidh Nashiruddin Al-Bakry (Pringgitan, 2022)
Catering is knowledge in the culinary field (the art of cooking food) which covers the scope of food, from preparation to serving the food itself, both traditional and international. The role of the instructor is very important to improve and adjust the absorption of students. Instructors can be creative in the form of activities that are appropriate and sourced from the social and natural environment. This study aims to determine how the application of the food plating method to increase student motivation in serving Indonesian cuisine. The form of research is descriptive method with qualitative analysis. From the application of the Food Plating method that is taught there are several obstacles faced, namely (1) Students can serve Indonesian cuisine with an attractive presentation and international class and (2) Students are more motivated in serving a dish with high artistic value. It was concluded that the application of the Food Plating Method could increase students' motivation in serving a dish. In addition, students of LKP Duta Persada must have a high artistic spirit.Keywords: Food Plating, Student Motivation, Indonesian Cuisine